Auto brand building successful car brands for the future - Parment, Anders 1972- (Kogan Page, 2014)
The car - once everybody's dream and a key status symbol in most countries and cultures - has been extensively questioned in the last decades and in the last few years particularly. Urbanisation, traffic congestion, pollution problems, heavy reliance on scarce oil supplies, safety issues and ever-growing competition, have all provided significant business challenges for the automotive industry. Many car manufacturers have had to fundamentally rethink their design, brand and marketing strategies to thrive in a savvy, consumer-led culture, and markets that are becoming increasingly restrictive in size and opportunity. Auto Brand provides a roadmap to branding and marketing success in the automotive industry from a leading industry expert and features: case studies on major car brands personally conducted by the author including: Audi, BMW, Holden, Mercedes-Benz, Opel, Porsche, Saab, Seat, Skoda, Vauxhall, Volkswagen, and Volvo; the findings from 100 interviews conducted with CEOs, marketing managers, sales managers, sales people, after sales managers at all levels from the manufacturer level to small rural dealers, as well as industry experts, policy makers, free-stranding repair shops and professional organizations; and the results of a new international study on car buyer behaviour based on 4,700 survey answers. Auto Brand is essential reading for marketing managers, sales managers, CEOs, development managers and dealers in all types of companies in the car industry including: manufacturers, national sales companies/importers, dealers, finance companies, insurance companies, free-standing repair shop channels and more. The first book to specifically address how to deal with the challenges facing the automotive industry it illustrates how companies can take advantage of new technologies, adapt to emerging trends in consumer behaviour, improve profitability and build even more successful brands in the future.